Immunopathogenesis of corneal graft rejection - Prafulla Kumar Maharana; Sohini Mandal; Luci Kaweri; Pranita Sahay; Suman Lata; Mohamed Ibrahime Asif; Ritu Nagpal; Namrata Sharma (Indian Journal of Ophthalmology, 2023)
The most common cause of corneal graft failure is corneal graft rejection (CGR). Although cornea is one of the immune-privileged sites, it can still get a rejection episode due to a breach in its natural protective mechanism. Both anatomical and structural properties of cornea and anterior chamber contribute toward its immune tolerance. Clinically, every layer of the transplanted cornea can get a rejection episode. A proper understanding of immunopathogenesis will help in understanding the various mechanism of CGR and the development of newer strategies for the prevention and management of such cases.